2017
DOI: 10.1515/helm-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic infections of anurans from a freshwater creek community in Delta State, Niger Delta of Nigeria

Abstract: SummaryThe parasitic infections of 125 anurans belonging to 13 taxa from Ase community in Delta State in the Niger Delta of Nigeria was investigated. An overall prevalence of 77.6% was recorded and the 32 parasites recovered included one pentastomid, four cestode, four monogenean, ten digenean and thirteen nematode taxa. Among the anurans examined, Ptychadena bibroni harboured the highest number of parasites. Most of the parasites encountered were adults but some occurred as larvae, which either used the amphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
2
11
1
Order By: Relevance
“…Moreover, this is also the season when the arthropod intermediate host of some parasites occur in their abundance to effect their trophic transmission to their definitive hosts. This pattern of infection has also been observed by other authors (Aisien et al, 2001(Aisien et al, , 2011(Aisien et al, , 2017.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, this is also the season when the arthropod intermediate host of some parasites occur in their abundance to effect their trophic transmission to their definitive hosts. This pattern of infection has also been observed by other authors (Aisien et al, 2001(Aisien et al, , 2011(Aisien et al, , 2017.…”
Section: Resultssupporting
confidence: 89%
“…Gassmann (1975) (Causey, 1939). The same observation was made by Aisien et al (2017), who reported two Folleyellides species in the anurans investigated at Ase, a location in the Niger Delta of Nigeria. The authors remarked that the high prevalence/intensity infection of these nematodes (47.7%/10.2 worms per infected host) bore direct relationship with the high population of mosquitoes observed the locality.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This low infestation rate of Trematodes of the genus Mesocoelium in the sampling, could be explained by the absence of its host-type in the study area. Indeed, previous studies have shown that the highest prevalence of Trematodes of genus Mesocoelium had been recorded in areas dominated by the species of Amnirana galamensis (Aisien et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…While most of the parasites recovered were adults, some larval stages that use anurans either as intermediate or paratenic hosts were also encountered. Polystoma galamensis, a monogenean commonly associated with host species Amnirana galamensis from the savannah biotope [24,25], was recorded in this location, albeit with low prevalence and infection intensity [50]. Although Amnirana galamensis was considered an accidental host for the larval brachylaimid recovered in this frog, this infection led to the unraveling of the intermediate and definitive hosts of this trematode in the creek environment (M.S.O.…”
Section: Freshwater Creeksmentioning
confidence: 99%